Performance Analysis of a 220 V DC Lead-Acid Battery Using the Dummy Load (Torkel 840) Method in The Electrical System of a Steam Power Plant 2x 100 MW - Witri Onanda; Muhardika; Resti Savira; Akbar Abadi; Anisa Amir (Andalasian International Journal of Applied Science, Engineering and Technology, 2026)
Battery performance can be affected by operational disturbances such as overcharging and deep discharging, which may lead to voltage instability, temperature rise, and accelerated degradation. This study analyzes the effect of discharge current on the voltage and temperature characteristics of a lead-acid battery in a 220 V DC LAA system using a dummy load method. The experimental test was conducted using a Torkel 840 battery discharge tester with a constant discharge current of 25 A for a duration of 10 hours. Parameters including total battery voltage, average cell voltage, battery temperature, and electrolyte specific gravity were measured periodically during the discharge process. The minimum allowable battery voltage was determined based on manufacturer specifications to ensure safe operation. The results indicate that the battery voltage decreased gradually and remained above the minimum allowable limit of 187.2 V, demonstrating stable voltage performance under constant load conditions. Battery temperature increased moderately from 22.36 °C to 25.93 °C and remained within the recommended operating range. The electrolyte specific gravity showed a consistent decrease corresponding to normal electrochemical behaviour. These results confirm that the tested lead-acid battery is suitable for reliable operation as a DC backup power source in power plant applications.